Family and School Integration in the Development of the Creativity Component in Students Based on Collaboration Technology - Ortikova Zulfiya Nurmuhammatovna; Exsonaliyeva Madinabonu (Zien Journals, 2023)
this article talks about the fact that cooperation technology is an activity aimed at making certain changes in the practice of educational institutions to develop the creativity component in students.
Keywords: cooperation technology; creativity; component